2013
DOI: 10.1111/jcpe.12196
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin resistance and periodontitis in Korean adults

Abstract: Our results suggest that insulin resistance may be associated with periodontitis, especially when combined with obesity, among post-menopausal women in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 53 publications
0
34
1
Order By: Relevance
“…Further, the mean value of HOMA-IR in subjects without diabetes in the current study did not differ significantly between periodontitis and non-periodontitis subjects, while the earlier findings reported slightly higher mean values of HOMA-IR in non-periodontitis male participants [21]. However in the current study decreased β-cell function was found in participants with periodontitis among participants without diabetes and periodontitis was an independent risk factor for decreased HOMA-β which might lead to IFG and diabetes.…”
Section: Baseline Characteristics Of Participants Without Diabetes Accontrasting
confidence: 48%
See 1 more Smart Citation
“…Further, the mean value of HOMA-IR in subjects without diabetes in the current study did not differ significantly between periodontitis and non-periodontitis subjects, while the earlier findings reported slightly higher mean values of HOMA-IR in non-periodontitis male participants [21]. However in the current study decreased β-cell function was found in participants with periodontitis among participants without diabetes and periodontitis was an independent risk factor for decreased HOMA-β which might lead to IFG and diabetes.…”
Section: Baseline Characteristics Of Participants Without Diabetes Accontrasting
confidence: 48%
“…In addition, further study assessed the relationship between impaired fasting glucose (IFG) and chronic periodontitis [20]. Recent study has revealed that periodontitis prevalence is proportional to the HOMA-IR in women at post-menopausal status, although this type of link was not found in men and pre-menopausal women in Korean adults [21]. Hence, the current study helps us in understanding the risk factors associated with periodontitis, specifically, whether periodontitis is associated with IR and pancreatic β-cell deregulation that leads to IFG in the general Korean population from a representative number of samples.…”
Section: Clinicalmentioning
confidence: 99%
“…Benguigui et al (2010) found that only HOMA-IR was associated with severe periodontitis and greater number of sites with CAL≥4 mm, CAL≥5 mm, and PPD≥4 mm; however, these associations disappeared among non-smokers. Lim et al (2014) found that postmenopausal women who were in the highest quartile of HOMA-IR were more likely to have periodontitis; however, the association was not seen among men nor premenopausal women. Timonen et al (2011) found that the association between HOMA-IR and periodontitis disappeared after controlling for BMI.…”
Section: Discussionmentioning
confidence: 83%
“…A pilot case-control study found that mean HbA1c was significantly higher in periodontitis cases than in healthy controls (Wolff et al, 2009). The insulin resistance-periodontitis association has been investigated in six cross-sectional studies (Song et al, 2016; Demmer et al, 2012; Islam et al, 2015; Benguigui et al, 2010; Lim et al, 2014; Timonen et al, 2011) and one longitudinal study (Timonen et al, 2013) and have produced mixed results. The one-hour post-load plasma glucose (1hPG) concentration during the oral glucose tolerance test has been shown to correlate strongly with predictors of diabetes and abnormal glucose homeostasis (Abdul-Ghani et al, 2008; Joshipura et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed the association of periodontitis with insulin resistance56, cardiovascular disease7, gastric Helicobacter pylori infection8 and liver fibrosis in patients with hepatitis virus infection9. The presence of periodontitis is considered a risk factor for these chronic diseases.…”
mentioning
confidence: 99%